Implementation of the Job Creation Law: Severance Pay from the Perspective of Pressman and Wildavsky's Theory - Katanging, Deva Garcia; Nabila, Nabila; Putri, Siska Aulia; Viona, Merry; Sinaga, Lina Sahida BR (Journal Governance Bureaucratic Review, 2025)
This study examines the bureaucratic dynamics underlying the implementation of severance pay regulations under Indonesia’s Job Creation Law (Law No. 11 of 2020). The reform, designed to streamline labor policies and enhance flexibility, has raised significant debates concerning workers’ protection and the government’s administrative readiness. The research aims to analyze how bureaucratic communication, institutional capacity, and inter-agency coordination affect the effectiveness of the Job Loss Guarantee (Jaminan Kehilangan Pekerjaan or JKP) scheme. Using a qualitative descriptive approach, data were collected through semi-structured interviews, document analysis, and observation of coordination meetings involving officials from the Ministry of Manpower, BPJS Ketenagakerjaan, regional labor offices, and labor unions. Thematic analysis based on Pressman and Wildavsky’s (1973) policy implementation model was applied to assess communication flows, resource adequacy, and structural mechanisms. The findings reveal that fragmented communication, uneven institutional capacity, and weak coordination have hindered consistent policy implementation across regions. Insufficient digital infrastructure and inadequate policy socialization further reduced administrative efficiency and worker awareness. The study concludes that effective reform requires integrated digital communication systems, continuous capacity building, and participatory coordination frameworks. Strengthening bureaucratic communication and institutional readiness is essential for translating the regulatory intent of the Job Creation Law into tangible improvements in worker protection and welfare.